The Effect of Digital Competence, Social Capital, Emotional Intelligence on Teacher Performance through Job Satisfaction - Nelly Chandrawati Manalu (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of digital competence, social capital, and emotional intelligence on teacher performance, with job satisfaction as a mediating variable. The main focus is to provide recommendations to senior high school principals to improve teacher competence as a whole in order to support the effectiveness of school organizations in the digital era. This study uses a quantitative approach, with data collection through questionnaires to 389 senior high school teachers in Batam City. Data analysis was carried out using the Structural Equation Modeling–Partial Least Square (SEM-PLS) technique using SmartPLS 3.0 software. The results showed that social capital has a positive and significant effect on teacher performance. Strong social capital creates a conducive working atmosphere, mutual trust, and supports collaboration between teachers. Conversely, emotional intelligence does not have a direct effect on performance, but has a positive and significant effect on job satisfaction, which in turn can mediate the improvement of teacher performance. Job satisfaction is not proven to mediate the effect of social capital on teacher performance, because the direct effect is greater than the indirect effect. This study concludes that strengthening social capital and digital competence directly has a positive impact on improving teacher performance, while emotional intelligence plays a greater role in shaping job satisfaction. These findings provide a basis for school leaders to design human resource development policies that consider social and psychological factors in improving teacher performance in the era of digital transformation.